A specific notation for contrast medium and dehydrated ethanol injection into the vein of Marshall during mitral isthmus ablation—A case report. Issue 1 (13th September 2022) - Zhang, Wei; Li, Xinyun; Su, Guoying; Gao, Xiaoyuan; Kong, Qingzan
Abstract: Background: Ablation of the vein of Marshall (VOM) by dehydrated ethanol (DE) is an important method for completely blocking the mitral isthmus (MI). Before DE ablation of the VOM, Marshall angiography should be performed so that the contrast medium is inevitably exposed to DE. Method: We present a case of DE ablation of the VOM. When iodixanol was exposed to DE, some floccule embolized the lumen of the over‐the‐wire (OTW) balloon dilatation catheter and led to the impossibility of DE ablation. Then, we performed in vitro experiments: iodixanol, not iomeprol, produced many stable white floccules when it encountered DE. Conclusion: Iodixanol is not an appropriate contrast for DE ablation of the VOM. However, if there is no other alternative contrast, the following methods might be used to address the problem: ⑴ diluted iodixanol (iodixanol:normal saline 1:1) could be used for VOM ablation; or ⑵ the lumen of the OTW could be flushed by NS after VOM angiography, and then DE injection could be performed.